Rhythmic expression of cryptochrome induces the circadian clock of arrhythmic suprachiasmatic nuclei through arginine vasopressin signaling - Edwards,MD; Brancaccio,M; Chesham,JE; Maywood,ES; Hastings,MH (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Circadian rhythms in mammals are coordinated by the suprachiasmatic nucleus (SCN). SCN neurons define circadian time using transcriptional/posttranslational feedback loops (TTFL) in which expression of Cryptochrome (Cry) and Period (Per) genes is inhibited by their protein products. Loss of Cry1 and Cry2 stops the SCN clock, whereas individual deletions accelerate and decelerate it, respectively. At the circuit level, neuronal interactions synchronize cellular TTFLs, creating a spatiotemporal wave of gene expression across the SCN that is lost in Cry1/2-deficient SCN. To interrogate the properties of CRY proteins required for circadian function, we expressed CRY in SCN of Cry-deficient mice using adeno-associated virus (AAV). Expression of CRY1::EGFP or CRY2::EGFP under a minimal Cry1 promoter was circadian and rapidly induced PER2-dependent bioluminescence rhythms in previously arrhythmic Cry1/2-deficient SCN, with periods appropriate to each isoform. CRY1::EGFP appropriately lengthened the behavioral period in Cry1-deficient mice. Thus, determination of specific circadian periods reflects properties of the respective proteins, independently of their phase of expression. Phase of CRY1::EGFP expression was critical, however, because constitutive or phase-delayed promoters failed to sustain coherent rhythms. At the circuit level, CRY1::EGFP induced the spatiotemporal wave of PER2 expression in Cry1/2-deficient SCN. This was dependent on the neuropeptide arginine vasopressin (AVP) because it was prevented by pharmacological blockade of AVP receptors. Thus, our genetic complementation assay reveals acute, protein-specific induction of cell-autonomous and network-level circadian rhythmicity in SCN never previously exposed to CRY. Specifically, Cry expression must be circadian and appropriately phased to support rhythms, and AVP receptor signaling is required to impose circuit-level circadian function.